(untitled) (Eastern Journal of Medical Sciences, 2017)
Water is the portal on entry of many infections and hence, should be safe for drinking. There are several methods of water sanitation, such as filtration, boiling, and ultraviolet light. Hence, safe drinking water is very important for prevention of illnesses such as diarrhea and dysentery.